The Influence Of Marketing Strategies Through Social Media On Purchase Decisions Of Perfume Products (A Case Study At Alap Perfume Store In Talang Jawa Lahat) - Yerica Rahmadania; Melia Andayani; Saparudin Saparudin (Journal of Management, Economic, and Accounting, 2026)
This research aims to determine the influence of social media marketing strategies on purchasing decisions for Alap Perfume products in Talang Jawa Lahat. The population in this study consists of all consumers who purchased Alap Perfume products in Talang Jawa Lahat during the period from August 2024 to March 2025, totaling 601 people. The sampling technique used was accidental sampling with the Slovin formula, resulting in 86 respondents as the research sample. Data collection was carried out using questionnaires with a Likert scale. The type of research employed was associative quantitative research, analyzed using simple linear regression, t-test, correlation coefficient, and coefficient of determination with the SPSS version 25 software. The results showed that social media marketing strategies have a positive and significant effect on purchasing decisions for Alap Perfume products in Talang Jawa Lahat.